Jet-fuel range hydrocarbon production from Reutealis trisperma oil over Al-MCM-41 derived from Indonesian Kaolin with different Si/A1 ratio - Nugraha, Reva Edra; Prasetyoko, Didik; Nareswari, Nabila Argya; Aziz, Abdul; Holilah, Holilah; Bahruji, Hasliza; Yusop, Muhammad Rahimi; Asikin-Mijan, Nurul; Suprapto, Suprapto; Taufiq-Yap, Yun Hin; Abdul Jalil, Aishah; Purnami, Santi Wulan; et al. (Elsevier, 2024)
The catalytic conversion of Reutealis trisperma oil was carried out over a Al-MCM-41 based catalyst with different Si/Al ratio with no added hydrogen to examine the possibility of the direct production of hydrocarbons in the ranges of jet fuel. In a semi-batch reactor, RTO was combined with 3 % catalyst and heated to 350 °C for 4h. The blank reaction shows the lowest conversion and liquid yield, with values of 39.65 % and 8.74 %, respectively. In contrast, the highest conversion was achieved using the Al-MCM-41 (30) catalyst, and the conversion decreases as the Si/Al ratio of the Al-MCM-41 catalyst increases. Indeed, the mesoporous structure enabled extensive bio-oil diffusion and adsorption, further increasing catalytic conversion. The Al-MCM-41 (30) shows the great performance in catalytic conversion of RTO to hydrocarbon and aromatic chain hydrocarbon. The Al-MCM-41 (30) catalyst resulted in a composition of 41.26 % paraffin, 6.78 % olefin, 21.77 % arenes, and 11.44 % cycloparaffin. This composition is comparable to JP-8 and Jet-A fuels, satisfying the ASTM D7566 standard for aircraft turbine fuel containing synthetic hydrocarbons. The acid site and pore size on the support material influenced the interaction of bio-oil molecules and catalyst which increasing the rate of reactant/product diffusion and improve the jet-fuel production. The obtained results are promising for the use of non-edible RTO and kaolin-derived catalysts in the production of sustainable alternative jet fuels. This approach offers competitive costs and significant environmental and social benefits. © 2024 The Authors